The Heterogeneity of Symptom Burden and Fear of Progression Among Kidney Transplant Recipients: A Latent Class Analysis - Zhang Y; Liu S; Miao Q; Zhang X; Wei H; Feng S; Li X (Psychology Research and Behavior Management, 2024)
Ying Zhang,* Sainan Liu,* Qi Miao, Xu Zhang, He Wei, Shuang Feng, Xiaofei Li The First Affiliated Hospital of China Medical University, Shenyang, 110001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaofei Li, Transplantation and Hepatobiliary Department, The First Affiliated Hospital of China Medical University, Shenyang, 110001, People’s Republic of China, Tel +15940564748, Email lixiaofei0603@aliyun.comPurpose: Kidney transplant recipients (KTRs) may experience symptoms that increase their fear of progression (FoP), but a dearth of research examines the issue from a patient-centered perspective. Our study aimed to first determine the category of symptom burden, then to explore the differences in characteristics of patients in different subgroups, and finally to analyze the impact of symptom subgroup on FoP.Patients and Methods: Sociodemographic and Clinical Characteristics, Symptom Experience Scale, and Fear of Progression Questionnaire-Short Form were used. Latent class analysis was used to group KTRs according to the occurrence of symptoms. We used multivariate logistic regression to analyze the predictors of different subgroups. The differences in FoP among symptom burden subgroups were analyzed by hierarchical multiple regression.Results: Three subgroups were identified, designated all-high (20.5%), moderate (39.9%), and all-low (39.6%) according to their symptom occurrence. Multivariate logistic regression showed that gender, post-transplant time, per capita monthly income, and hyperuricemia were the factors that distinguished and predicted the all-high subgroup (P < 0.05). Hierarchical multiple regression showed that symptom burden had a significant effect on FoP (class1 vs class3: β = 0.327, P < 0.001; class2 vs class3: β = 0.104, P = 0.046), explaining the 8.0% variance of FoP (ΔR2 = 0.080).Conclusion: KTRs generally experience moderate or low symptom burden, and symptom burden is an influencing factor in FoP. Identifying the traits of KTRs with high symptom burden can help clinicians develop targeted management strategies and ease FoP of KTRs.Keywords: kidney transplant, symptom burden, fear of progression, latent class analysis